Il profilo del partner maltrattante - Luca Cimino (Rivista di Criminologia, Vittimologia e Sicurezza)
Intimate partner violence (IPV) is one of the most common forms of violence against women and includes physical, sexual, emotional abuse and controlling behavior by an intimate partner. Through a careful analysis of the phenomenon, it is possible to detect the real criminogenic diriment of the perpetrator-victim relationship within the motivations that led to the crime and, through them, the psychological and functional characteristics of the abuser, can be identified. What makes the recognition of an aggressive personality most difficult is the moment of its explicit manifestation, which often takes place at an advanced stage of the relationship, when mutual investments have increased, and ties are more difficult to break. In most cases, however, violent behavior does not arise suddenly but has been heralded by a series of overt and covert attitudes with a nonnegligible predictive value. Although it is not possible to identify a prototypical psycho(patho)logical profile of the abusive partner, against whom in the vast majority of cases it is not possible to find a defined clinical condition, nevertheless it seems possible to detect in the IPV perpetrators a common denominator that feeds a “perverse” dimension of the interpersonal relationship in which, that is, it is possible to identify a distortion of the functioning of “object relations”, followed by problems in the formation of the ego and with the structuring of pathological forms of attachment that, by preventing the processing of abandonment issues, may also cause violent behaviors. This article aims to analyze the pathways that lead to the structuring of the psycho(patholo)gic configurations most frequently found in abusive individuals not only to better understand the phenomenon of IPV, but also to outline appropriate preventive actions.